Medical College Student’s Knowledge, Attitude, and Practice Regarding Organ Donation - A Multi Centre Study B H (Northern International Medical College Journal, 2025)
Background: Organ donation is the process of retrieving healthy organs and tissues from a living or deceased person for transplantation into another individual in need. It plays a vital role in saving lives and improving the quality of life for patients suffering from organ failure such as kidney, liver or heart. Methods: This descriptive cross-sectional study was conducted from 21st to 31st October 2024 among final-year students of Anwar Khan Modern Medical College (AKMMC), Green Life Medical College (GLMC), and Northern International Medical College (NIMC). The knowledge, attitude, and practice (KAP) of the students regarding organ donation were assessed using 10 questions on knowledge, 10 on attitude, and 6 on practice, assigning a score of 1 for each correct response and 0 for each incorrect response. Purposive sampling technique was used for data collection and the final sample size was 261. The data were analysed via SPSS (version 25.0) p < 0.05 was considered statistically significant. Results: The study population included 61.3% females and 38.7% males with a mean±SD age of 24.5±1.5 years. AKMMC represented almost half of the participants (48.3%), while GLMC and NIMC accounted for 31.4% and 20.3% of the participants, respectively. The majority of the participants (88.9%) were from urban areas, while only 11.1% were from rural areas. Association between gender and participants’ knowledge regarding organ donation was significant (p = 0.02), while their attitude towards and practice regarding organ donation was not significant (p> 0.05). Females were more knowledgeable than male. Association between medical college and participants’ knowledge, attitude, and practice regarding organ donation was not significant (p > 0.05). Association between residence and participants’ knowledge and practice regarding organ donation was significant (p = 0.01), while their attitude towards organ donation was not significant (p > 0.05) Conclusion : The results of our study revealed that the majority of the participants had a satisfactory level of knowledge, showed a positive attitude, but had poor practice regarding organ donation. The majority first heard about organ donation from the internet and were aware that kidney, liver, heart, lung, cornea and bone can be donated. As most of the participants lacked knowledge about ‘The Human Organ Transplantation Act’ of Bangladesh, awareness programs and activities should be arranged to discuss its details.Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 706-711